2011
DOI: 10.1002/jbmr.358
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Dickkopf-2 levels contribute to the abnormal phenotype of human osteoarthritic osteoblasts

Abstract: The Wnt signaling pathway is crucial for osteogenesis and regulates terminal osteoblast differentiation. Although osteoarthritic (OA) osteoblasts show an abnormal phenotype and poor in vitro mineralization, the mechanism leading to this situation still remains unknow. Recent evidence indicates that Wnt signaling may be altered in OA osteoblasts. In this study we determined whether an alteration of the Wnt/b-catenin signaling pathway is responsible for the abnormal phenotype of OA osteoblasts. Expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 49 publications
(101 reference statements)
4
75
0
2
Order By: Relevance
“…Among members of the Dkk family, Dkk-1 is known to inhibit the canonical Wnt pathway, whereas Dkk-2 inhibition of this pathway depends on cellular context (11). For instance, Dkk-2 blocks the Wnt-1-dependent canonical pathway in OA osteoblasts (12), while it is also known to activate ␤-catenin signaling in Xenopus embryos (13). These opposing effects of Dkk-2 appear to be modulated by kremen 2, which converts Dkk-2 from an agonist to an antagonist of LRP-6 (14).…”
mentioning
confidence: 99%
“…Among members of the Dkk family, Dkk-1 is known to inhibit the canonical Wnt pathway, whereas Dkk-2 inhibition of this pathway depends on cellular context (11). For instance, Dkk-2 blocks the Wnt-1-dependent canonical pathway in OA osteoblasts (12), while it is also known to activate ␤-catenin signaling in Xenopus embryos (13). These opposing effects of Dkk-2 appear to be modulated by kremen 2, which converts Dkk-2 from an agonist to an antagonist of LRP-6 (14).…”
mentioning
confidence: 99%
“…Еще одним следствием этого процесса является из-менение фенотипа и нарушение функции остеобластов и остеокластов СХК [32,33], которые продуцируют различ-ные цитокины, факторы роста, ПГ и ЛТ, инициирующие деградацию суставного хряща [34,35]. Усиление локально-го синтеза ИЛ1, ИЛ6, ФНО и ИЛ17 также способствует ус-корению остеокластогенеза и костной резорбции [36,37].…”
Section: таблицаunclassified
“…Early observations of OA bone tissue samples reported increased levels of TGF-β1 and IGF-1 even in non-weight-bearing joints, implying that OA could be a bone disease. Moreover, TGF-β1 levels remain elevated in isolated bone explants and in vitro osteoblasts of OA patients 41,44 . A recent study indicated that targeted overexpression of TGF-β1 in mouse osteoblasts, but not in other joint tissues, lead to OA-like features, whereas inhibition of TGF-β1 activity in subchondral bone prevented the degeneration of articular cartilage in these mice 64 .…”
Section: Role Of the Wnt Signalling Pathway In Msc Lineage Commitmentmentioning
confidence: 99%